Ecological Literacy Leadership: Into the Mind of Nature. Issue 1 (1st January 2014) - Kineman, John J.; Poli, Roberto
Abstract : A broad international agenda for research and education in systemic sustainability, holism, and anticipation is needed to meet the challenges of sustainability science and to anticipate a better future. We propose a new scientific and cultural framework for this agenda based on the need to couple "bottom‐up" and "top‐down" causation to understand complex and living systems as more than mechanisms; involving complex feedbacks and information relations with multiple simultaneous contexts. The initial framework, which is itself a subject of investigation, is based on categorical relations between natural forms of information and material phenomena—a new vision of science and nature that is emerging in all fields today. The necessary coupling of essential "causes" or modes of explanation, can be accomplished rigorously and mathematically using the approach of relational biology pioneered by the mathematical biologist Robert Rosen. This approach suggests a deep natural foundation in the sciences that is quintessentially ecological, introducing a principle of natural relation and anticipation involving "closed loops of causation" that cannot exist as traditional mechanisms. The new agenda aims to understand "systemic sustainability" in proper balance with "process sustainability, " which tends to dominate sustainability research and practice today. At the same time, new organizational learning and entrepreneurship models are changing management, business, education, and social science toward more creative modes of functioning. These are met with a similar call for new models in education. The education agenda we envision will seek a balance between top‐down and bottom‐up modes of learning, perhaps following the example of "Learning Organization"; thus being largely student‐driven, interdisciplinary, multi‐cultural, experience based, and yet theory oriented as an open laboratory to discover natural principles of whole system function. Here we present an initial framework for this "Ecological Literacy Leadership" agenda, which will be further described in future papers.